Nasal Saline Irrigation with vs. without Additives in Chronic Rhinosinusitis: A Trial of Symptom Relief and Mucociliary Clearance - Muhammad Wahid Saleem, Muhammad Awais Samee, Aysha Nauman, Muhammad JamilAnees Ur Rehman, Muhammad Tahir Shah (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Chronic rhinosinusitis (CRS) significantly impairs quality of life due to persistent inflammationand impaired mucociliary function. Nasal saline irrigation is a standard adjunctive therapy, yet thebenefit of adding agents such as sodium bicarbonate